Colorectal cancer screening in newly insured Medicaid members: a review of concurrent federal and state policies - Meghan C. O'Leary; Kristen Hassmiller Lich; Yifan Gu; Stephanie B. Wheeler; Gloria D. Coronado; Sarah E. Bartelmann; Bonnie K. Lind; Maria E. Mayorga; Melinda M. Davis (BMC, 2019)
Abstract Background Colorectal cancer (CRC) screening is underutilized by Medicaid enrollees and the uninsured. Multiple national and state policies were enacted from 2010 to 2014 to increase access to Medicaid and to promote CRC screening among Medicaid enrollees. We aimed to determine the impact of these policies on screening initiation among newly enrolled Oregon Medicaid beneficiaries age-eligible for CRC screening. Methods We identified national and state policies affecting Medicaid coverage and preventive services in Oregon during 2010-2014. We used Oregon Medicaid claims data from 2010 to 2015 to conduct a cohort analysis of enrollees who turned 50 and became age-eligible for CRC screening (a prevention milestone, and an age at which guideline-concordant screening can be assessed within a single year) during each year from 2010 to 2014. We calculated risk ratios to assess whether first year of Medicaid enrollment and/or year turned 50 was associated with CRC screening initiation. Results We identified 14,576 Oregon Medicaid enrollees who turned 50 during 2010-2014; 2429 (17%) completed CRC screening within 12 months after turning 50. Individuals newly enrolled in Medicaid in 2013 or 2014 were 1.58 and 1.31 times more likely, respectively, to initiate CRC screening than those enrolled by 2010. A primary care visit in the calendar year, having one or more chronic conditions, and being Hispanic was also associated with CRC screening initiation. Discussion The increased uptake of CRC screening in 2013 and 2014 is associated with the timing of policies such as Medicaid expansion, enhanced federal matching for preventive services offered to Medicaid enrollees without cost sharing, and formation of Medicaid accountable care organizations, which included CRC screening as an incentivized quality metric.